GAMMA DISTRIBUTION APPLICATION OF PARAMETER ESTIMATION METHOD BASED ON WEIBULL AUXILIARY MODEL (MT) - XIAO ShiHai; JIANG RenYan (Jixie qiangdu)
Since there are more systems to be observed on the sites and the observation time is shorter than the average life of the product, the life data actually collected is often heavily censored data. For such data, the classical parameter estimation methods can’t provide accurate and robust estimation. For this reason, a parameter estimation method based on the Weibull auxiliary model is proposed, and the numerical experiment results validate that this method can provide a more accurate and robust estimation of the gamma distribution than the classical parameter estimation method under the condition of heavily censored data.